1988
DOI: 10.1159/000177408
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Serum Concentration of Vitamin E in Alcoholics

Abstract: The effect of heavy alcohol consumption on serum concentrations of vitamin E (α-tocopherol) and selenium was studied in 13 alcoholics and 19 control subjects. Ethanol intake during the year previous to the study was in the range from 22 to 354 g/day and from 0 to 16 g/day among the alcoholics and controls, respectively. Of the 13 alcoholics, 6 had a serum concentration of α-tocopherol below the lower limit of reference (14 µmol/l) and mean serum concentration of α-tocopherol was reduced by 37% as compared to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Heavy consumption of ethanol reduced the plasma level of ·-tocopherol as well [12]. The serum concentration of ·-tocopherol was 30% lower in the alcoholics [13]; in another study it was reduced by 37% as compared to controls [11]. Such results support a role of free-radical-mediated damage, which can develop diseases frequently observed in alcoholics [11,80].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Heavy consumption of ethanol reduced the plasma level of ·-tocopherol as well [12]. The serum concentration of ·-tocopherol was 30% lower in the alcoholics [13]; in another study it was reduced by 37% as compared to controls [11]. Such results support a role of free-radical-mediated damage, which can develop diseases frequently observed in alcoholics [11,80].…”
Section: Discussionmentioning
confidence: 80%
“…The serum concentration of ·-tocopherol was 30% lower in the alcoholics [13]; in another study it was reduced by 37% as compared to controls [11]. Such results support a role of free-radical-mediated damage, which can develop diseases frequently observed in alcoholics [11,80]. Reduced serum levels of ·-tocopherol in alcoholics may be normalized by vitamin E supplementation [13].…”
Section: Discussionmentioning
confidence: 81%
“…The fate of antioxidants in an environment of oxidative stress resulting from chronic ethanol consumption is well documented. The vast majority of previous studies found a reduction in vitamin E levels associated with ethanol consumption (Bjorneboe and Bjorneboe, 1993; Bjorneboe et al., 1987a,b, 1988a,b; Grattagliano et al., 1997; Hartman et al., 2005; Johansson et al., 1986; Lecomte et al., 1994; Odeleye et al., 1991; Valls‐Belles et al., 2008), concluding the reduction resulted from either increased oxidative stress, differences in ethanol consumption or diet, altered lipoprotein status, or enzymatic changes in the liver. However, no other study has measured multiple indicators of vitamin E status.…”
mentioning
confidence: 96%
“…Additionally, chronic ethanol consumption leads to diminished plasma and liver concentrations of ATs (Meydani et al 1991), and an inverse correlation between hepatic lipid peroxidation and AT levels has been identified (Kawase et al, 1989;Sadrzadeh et al, 1994). Studies in alcoholics confirm the fact that alcohol reduces the concentrations of AT in serum and various tissues (Bjorneboe et al, 1988;Horvath et al, 1992).…”
Section: Discussionmentioning
confidence: 97%